Application Of Pes Fertilizer To The Growth Of Kappaphycus alvarezii Plantlets - Wahyudi, Dzikri; Pattirane, Chrisoetanto P.; Marwah, Ayu Riyani; Sangkia, Dony Frederik (Jurnal Ilmiah Platax, 2023)
This study aims to determine the growth of Kappaphycus alvarezii plantlets applied with different PES fertilizers. This research was conducted at Blitok Installation, brackish water aquaculture center, Situbondo. This study began with the preparation of water as a maintenance medium, acclimatization of plantlets in the greenhouse, maintenance of plantlets in the greenhouse (plantlet cleaning, fertilization), and checking water quality. The application dose of PES fertilizer given as treatment was 15 ml, 20 ml, and 25 ml which was repeated 3 times. The rearing design used a completely randomized design (CRD) model. The results obtained showed that the average absolute weight gain of planlets from the 15 ml treatment was 0.249 g - 0.271 g, the 20 ml treatment was 0.35 g - 0.432 g, and the 25 ml treatment ranged from 0.306 g - 0.372 g. For the specific growth rate from the first to the fifth week of rearing, the 15 ml treatment ranged from 3.162-1.693, the 20 ml treatment ranged from 3.922-4.21 and the 25 ml treatment ranged from 2.899-3.904. From the results of the study, it can be concluded that the application of a PES fertilizer dosage of 20 ml gave better growth than the 15 ml and 25 ml doses. Keywords: growth, Kappaphycus alvarezii, plantlets, PES fertilizer, dosage